Role of Remittances on Gross Domestic Product (GDP) Growth in Developing Countries: The Case of Bangladesh - Hossain, Md. Shahadat; Chin, Lee; Said, Rusmawati; Ishak, Suryati Binti (Journal of Reviews on Global Economics, 2020)
Bangladesh is one of the top ten remittance recipient countries and the contribution of remittance to the GDP has increased dramatically in recent years. This study examines the role of remittances on GDP growth in Bangladesh and Time series data for decades from 1996 to 2019 extracted from the World Bank database as well as Bangladesh Bank statistics were used. The study was conducted being motivated from conflicting results that have emerged in the literature on the impact of remittance on the economic growth of different countries. Using ordinary least squares (OLS) and Pearson correlation method, the empirical results of the study have been consistent with some previous studies while also contrasted to some literature on the impact of remittances on GDP, Gross Domestic Savings and Domestic Expenditure of a country. We have found that the remittances have a significant impact on the growth of GDP as well as Gross Domestic Savings and Domestic Expenditure. Since, there are no recent studies on the role of remittances on GDP, therefore, the findings of the study provide a significant insights for policymakers for strengthening policies and regulations relating to harnessing remittances for economic growth. Implications of the study have been discussed.